PENEGAKAN HUKUM TINDAK PIDANA BULLYING TERHADAP ANAK DI BAWAH UMUR BERDASARKAN UNDANG-UNDANG NOMOR 35 TAHUN 2014 (Causa: Jurnal Hukum dan Kewarganegaraan, 2025)
The crime of bullying against minors is a type of violence that severely disrupts the physical and mental development of children. Several laws and regulations in Indonesian criminal law regulate child bullying. These regulations provide special protection to children who are victims of criminal acts of bullying. The purpose of this study is to analyze law enforcement efforts against perpetrators of bullying crimes that target minors as victims and to evaluate how effective existing regulations are. Using normative juridical research methods, legislation, literature studies, and relevant cases. The results of the analysis show that Law Number 35 of 2014 concerning Child Protection generally regulates the protection of children who are victims of criminal acts of bullying.  And in certain conditions can also be charged through the Criminal Code (KUHP).  In addition, if the perpetrator of the criminal act of bullying is a child, then the handling refers to Law Number 11 of 2012 concerning the Child Criminal Justice System which prioritizes the principle of restorative justice.